2005
DOI: 10.1097/00000542-200503000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bispectral Index Monitoring on Recovery from Surgical Anesthesia in 1,580 Inpatients from an Academic Medical Center

Abstract: The use of BIS monitoring for inpatients undergoing a wide variety of surgical procedures in an academic medical center had some minor effects on intraoperative anesthetic use but had no impact on recovery parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 15 publications
3
13
1
1
Order By: Relevance
“…However, Pavlin et al. reported in a large, randomised clinical trial that although BIS monitoring was associated with a slight decrease in sevoflurane administration, it did not lead to faster emergence or a shorter stay in the postoperative recovery area . Similarly, analyses from the BAG‐RECALL and B‐Unaware trial populations and the Michigan Awareness Control Study demonstrated no difference in anaesthetic administration, time to discharge from the postoperative recovery area, or incidence of PONV with the use of BIS guidance compared with controls .…”
Section: Do Changes In Anaesthetic Management Affect Outcomes?mentioning
confidence: 99%
“…However, Pavlin et al. reported in a large, randomised clinical trial that although BIS monitoring was associated with a slight decrease in sevoflurane administration, it did not lead to faster emergence or a shorter stay in the postoperative recovery area . Similarly, analyses from the BAG‐RECALL and B‐Unaware trial populations and the Michigan Awareness Control Study demonstrated no difference in anaesthetic administration, time to discharge from the postoperative recovery area, or incidence of PONV with the use of BIS guidance compared with controls .…”
Section: Do Changes In Anaesthetic Management Affect Outcomes?mentioning
confidence: 99%
“…A reduction in sevoflurane administration was also reported with the use of entropy-guided monitoring [35,39], as well as with desflurane with Narcotrend monitoring [25]. BIS monitoring may help to reduce the incidence of postoperative nausea and vomiting [33,40,41]. In a metaanalysis [42] of BIS trials of ambulatory anesthesia in 1,390 patients across 11 randomized trials, BIS-guided anesthesia reduced anesthetic consumption by 19 %, reduced the occurrence of nausea/vomiting from 38 to 32 % in all patients, and reduced recovery time.…”
Section: Reductions In Drug Consumption and Postoperative Adverse Eventsmentioning
confidence: 95%
“…The trials showing benefit in this regard have generally been small efficacy trials (i.e., trials that show that pEEG-based protocols can improve postoperative recovery, including time to respond appropriately to commands, time to tracheal extubation, to eye opening, to leaving the operating room and to eligibility for discharge from the postanesthesia care unit). 31 Results from larger trials have not reproduced the same impressive successes, 23,32,33 and effectiveness data (i.e., trials that demonstrate whether pEEGs such as the BIS actually do improve outcomes such as postoperative recovery outside the context of a protocol-driven trial) are lacking. The B-Aware, B-Unaware and BAG-RECALL trials did not find that BIS monitoring was associated with administration of less anesthesia, decreased hospital stay or decreased mortality.…”
Section: Fast Track Cardiac Surgerymentioning
confidence: 99%